Gender-based Structural Stigma and Intimate Partner Violence Across 28 Countries: A Population-based Study of Women Across Sexual Orientation, Immigration Status, and Socioeconomic Status - Scheer, Jillian R. (Journal of interpersonal violence, 2022)
Reducing structural drivers of intimate partner violence (IPV), including gender inequity in education, employment, and health, surrounding women worldwide represents a clear public health priority. Within countries, some women are at disproportionate risk of IPV compared to other women, including sexual minority women, immigrant women, and women in poverty. However, limited research has assessed women?s IPV risk and related circumstances, including police involvement following IPV experiences and IPV-related worry, across sexual orientation, immigration status, and socioeconomic status in a population-based survey of women across countries. Further, few studies have examined IPV against minority women as a function of gender-based structural stigma. This study aimed to determine whether gender-based structural stigma is associated with IPV and related circumstances among European women; examine minority-majority IPV disparities; and assess whether structural stigma is associated with IPV disparities. We used the population-based 2012 Violence Against Women Survey (n = 42,000) administered across 28 European Union countries: 724 (1.7%) identified as sexual minority, 841 (2.0%) as immigrant, and 2,272 (5.4%) as living in poverty. Women in high gender-based structural stigma countries had a greater risk of past-12-month IPV (AOR: 1.18, 95% CI = 1.04, 1.34) and IPV-related worry (AOR: 1.09, 95% CI = 1.04, 1.15) than women in low structural stigma countries. All minority women were at disproportionate risk of IPV and IPV-related worry compared to majority women. Associations between gender-based structural stigma and IPV and related circumstances differed across minority status. Country-level structural stigma can possibly perpetuate women?s risk of IPV and related circumstances. Associations between structural stigma and IPV and related circumstances for sexual minority women, immigrant women, and women in poverty call for research into the IPV experiences of minority populations across structural contexts.